PERANCANGAN USER INTERFACE DAN USER EXPERIENCE APLIKASI BERBASIS MOBILE KLINIK KECANTIKAN MENGGUNAKAN METODE DESIGN THINKING (STUDI KASUS : KLINIK KATIA DERMA) - Shifa Silfiana; Imam Maruf Nugroho; Yudhi Raymond Ramadhan (INFOKOM (Informatika & Komputer), 2023)
The design of the User Interface and User Experience is very influential for user comfort, so accurate analysis is needed according to user needs. The Katia Derma Clinic is a clinic that is devoted to the treatment of facial skin health care and releases skincare products which are currently planning to create a mobile-based application. With the planning of making the application, the user interface and user experience will be designed first using the Design Thinking method. Testing the results of the design in this study was carried out using the User Experience Questionnaire (UEQ) testing method. Based on the test method used to test the design results in this study, positive results were obtained for all scales, namely the Attractiveness scale with a mean value of 2.028, Efficiency with a mean value of 2.075 and Dependability with a mean value of 1.725 included in the Excellent category, while the Perspicuity scale with a mean value of 1.825, Stimulation with a mean value of 1.525 and Novelty with a mean value of 1.225 are included in the Good category.